Relativistic particle dynamics in D = 2+1 - Valverde, Juan S. [UNESP]; Pazetti, Marcio [UNESP] (Springer Nature, 2006)
We propose a SUSY variant of the action for a massless spinning particles via the inclusion of twistor variables. The action is constructed to be invariant under SUSY transformations and τ-reparametrizations even when an interaction field is including. The constraint analysis is achieved and the equations of motion are derived. The commutation relations obtained for the commuting spinor variables λα show that the particle states have fractional statistics and spin. At once we introduce a possible massive term for the non-interacting model. © SISSA 2006.
Keywords: Field Theories in Lower Dimensions; Superspaces